Older adults in secure mental health care: health, social wellbeing and security needs measured with HoNOS-secure across different age groups. Issue 5 (3rd September 2018) - Girardi, Alessandra; Snyman, Pieter; Natarajan, Muthusamy; Griffiths, Christopher
ABSTRACT: The number of older offenders is rapidly increasing in the United Kingdom and some older adults with mental health issues are referred to secure care services. It is therefore important to understand their unique characteristics in order to develop services based on their individual needs rather than chronological age. This study explored wellbeing and security needs of younger and older patients admitted to a secure psychiatric hospital. HoNOS-secure assessment at admission and discharge was extracted and used to build an anonymous data-set. Group comparison and score change during admission were conducted for six age groups: 18–24, 25–34, 35–44, 45–54, 55–64 and 65+. Younger patients improved on most measures whereas older patients aged 55–65+ showed little improvement or deterioration over time. This finding suggests that the subscales are sensitive to age difference although the needs measured by HoNOS-secure are less likely to inform the decision to discharge.